Labor Market Modeling Recognizing Latent Job Attributes and Opportunity Constraints An Empirical Analysis of Labor Market Behavior of Eritrean Women - Marie W. Arneberg; John K. Dagsvik; Zhiyang Jia (Statistics Norway, Research Department, 2002)
This paper analyzes labor market behavior of urban Eritrean women with particular reference to the impact of education, earnings and labor market opportunities. Unlike traditional models of labor supply, which assume that work can be supplied freely in the labor market, we develop a framework that explicitly takes into account the notion of job opportunities and observable sets of feasible jobs. The framework is formulated within a random utility setting in which unobservable jobs can conveniently be treated as latent alternatives. The framework can also readily take into account observed restrictions on the sets of feasible jobs. The empirical estimation of the model is based on data from the labor force module of the 1996/97 Eritrean Household Income and Expenditure Survey for urban areas. We estimate structural choice probabilities of being in the states "Not employed", "Working in the wage sector", and "Working as self-employed", where it is taken into account that some women are constrained in their labor market choices. We find that the effect on wages of changes in education level is high; improving the education levels of women greatly improves their wages, which again contributes to bringing more women into the labor force. However, our data do not support the assumption that basic education increases women's job opportunities. In order to do so, at least secondary education is required.
Keywords: C25; J22; J31; 330; Female labor supply; Random utility model; Returns to education; Labor markets in developing countries.